Di-(2-ethylhexyl) phthalate limits the pleiotropic effects of statins in chronic kidney disease patients undergoing dialysis and endothelial cells. (December 2020) - Guo, Bei-Chia; Kuo, Ko-Lin; Chen, Chia-Hui; Chen, Shen-Liang; Tsou, Tsui-Chun; Lee, Tzong-Shyuan
Abstract: The level of di-(2-ethylhexyl) phthalate (DEHP) is elevated in chronic kidney disease patients undergoing dialysis. However, statins are unable to reduce the cardiovascular events in chronic dialysis patients. In this study, we investigated the effects of DEHP on statin-conferred pleiotropic effects and the underlying molecular mechanism in peritoneal dialysis (PD) patients and endothelial cells (ECs). In PD patients with serum DEHP level ≥0.0687 μg/mL, statin treatment was not associated with lower risk of cardiovascular disease. In ECs, exposure to DEHP abrogated the simvastatin-induced NO bioavailability and EC-related functions. Additionally, DEHP abolished the anti-inflammatory effect of simvastatin on the tumor necrosis factor α-induced upregulation of adhesion molecules and monocyte adhesion to ECs. Mechanistically, DEHP blunted the activation of transient receptor potential vanilloid type 1 (TRPV1), which is required for NO production by simvastatin in ECs. Notably, DEHP increased the activity and expression of protein phosphatase 2B (PP2B), a negative regulator of TRPV1 activity. The effect of DEHP on PP2B activation was mediated by the activation of the NADPH oxidase/reactive oxygen species (NOX−ROS) pathway. Inhibition of PP2B activity by pharmacological antagonists prevented the inhibitory effects of DEHP on simvastatin-induced Ca 2+ influx, NO bioavailability, and EC migration, proliferation, tube formation, and anti-inflammatory action. Collectively, DEHP activates the NOX−ROS−PP2B pathway, which in turns inhibits TRPV1/Ca 2+ -dependent signaling and abrogates the statin-conferred pleiotropic protection in ECs. Graphical abstract: Image 1 Highlights: The circulating levels of DEHP are increased in CKD patients with dialysis. Stains fail to reduce the risk of cardiovascular events in dialysis CKD patients. DEHP limits the pleiotropic effect of statins by increasing the generation of ROS. DEHP desensitizes the transient receptor potential vanilloid type 1 channels by ROS. This study proposes a novel causative role for DEHP in the failure of stain therapy.